CONTROL LOOP STUDY OF A LOAD COMMUTATED CSI-FED INDUCTION-MOTOR - SONG, JH; YOON, TW; KIM, KH; KIM, KB; YOUN, MJ (IEE-INST ELEC ENG, 1992)
This paper presents a systematic study for the induction motor drive system using a load commutated current source inverter (LCCSI). The steady state characteristics of a LCCSI-fed induction motor are shown to be the intermediate characteristics between the voltage source inverter (VSI) and the autosequentially commutated current source inverter (ASCI) systems. The dynamic characteristics of the LCCSI-fed induction motor are also investigated using a linearised model and the system control loops without a speed sensor are discussed. A study through the pole/zero locations of the linearised system shows that a V/Hz ratio feedback loop plays an essential role in the system stabilisation.